2014
DOI: 10.1093/bioinformatics/btu053
|View full text |Cite
|
Sign up to set email alerts
|

PUmPER: phylogenies updated perpetually

Abstract: Summary: New sequence data useful for phylogenetic and evolutionary analyses continues to be added to public databases. The construction of multiple sequence alignments and inference of huge phylogenies comprising large taxonomic groups are expensive tasks, both in terms of man hours and computational resources. Therefore, maintaining comprehensive phylogenies, based on representative and up-to-date molecular sequences, is challenging. PUmPER is a framework that can perpetually construct multi-gene alignments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…() developed PHLAWD to conduct a so‐called “baited” analysis where gene regions may be identified a priori thereby dramatically speeding up clustering analyses. This procedure was extended with PUmPER to allow for automatic updating when new sequences become available (Izquierdo‐Carrasco et al., ). Several newly developed software packages have built on these methods including SUMAC (Freyman, ) that incorporates both “baited” analyses and single‐linkage clustering methods as well as a novel means of determining when there are enough overlapping data, and SUPERSMART (Antonelli et al., ) that includes analyses from clustering to divergence‐time estimation.…”
mentioning
confidence: 99%
“…() developed PHLAWD to conduct a so‐called “baited” analysis where gene regions may be identified a priori thereby dramatically speeding up clustering analyses. This procedure was extended with PUmPER to allow for automatic updating when new sequences become available (Izquierdo‐Carrasco et al., ). Several newly developed software packages have built on these methods including SUMAC (Freyman, ) that incorporates both “baited” analyses and single‐linkage clustering methods as well as a novel means of determining when there are enough overlapping data, and SUPERSMART (Antonelli et al., ) that includes analyses from clustering to divergence‐time estimation.…”
mentioning
confidence: 99%
“…Pumper [29], which allows an automatic sequence retrieval and tree building, and Sativa [30], which automatically annotates sequences in a tree. Both depend on the quality of the initial input, highlighting the need for high-quality initial annotation as implemented in EukRef.…”
Section: The Eukref Curation Processmentioning
confidence: 99%
“…An increasing body of work mainly targets such taxonomic identification methods, with recent developments confronting the increasing scalability issues associated with the high dimensions of modern data sets (Barbera et al 2019;Czech et al 2018). Izquierdo-Carrasco et al (2014) implemented an online framework to estimate phylogenetic trees using maximum-likelihood heuristics, which automatically extends an existing alignment when sufficiently new data have been generated and subsequently reconstructs extended phylogenetic trees by using previously inferred smaller trees as starting topologies. The authors compared their methodology to de novo phylogenetic reconstruction and found a slight but consistent improvement in computational performance and a similar topological accuracy.…”
Section: Introductionmentioning
confidence: 99%